Genetic Contributors to Parkinson’s Disease and Vascular Parkinsonism in the Egyptian Population: Validation and Discovery Across the Parkinsonian Spectrum - ElShafie, Salma (AUC Knowledge Fountain, 2026)
Despite major advances in genomics of parkinsonism, individuals of Middle Eastern and North African ancestry -including Egyptians- remain markedly underrepresented in genetic studies. This gap limits our understanding of disease risk, phenotypic variability, and ancestry-specific genetic mechanisms. This dissertation addresses this gap by investigating the genetic determinants of parkinsonism in Egyptians through two projects: (1) evaluating the transferability and clinical relevance of a polygenic risk score model for Parkinson’s disease (PD), the most common form of parkinsonism, and (2) exploring rare, deleterious variants potentially contributing to vascular parkinsonism (VaP), one of the most frequent parkinsonian syndromes after PD. First, we assessed the performance of a European-derived PD polygenic risk score (PRS) comprising 90 genome-wide significant variants in 625 Egyptians, a genetically admixed population with African and European ancestral components. Despite known cross-ancestry limitations, the PRS significantly discriminated PD cases from controls (p=8.65×10-6) and remained robust in an age-matched subset (p=2.47×10⁻³). It was also associated with earlier age at onset (p=1.9 ×10⁻³) consistent with findings in European cohorts, and showed a suggestive association with greater disease severity (MDS-UPDRS total, p=0.0576) that became significant after excluding carriers of Mendelian pathogenic variants (p=0.0316). The associations of PRS with disease risk and age at onset persisted after conditioning on high-risk variants such as LRRK2 G2019S, supporting a broader polygenic contribution beyond single high-effect alleles. Incorporating novel PD loci from recent multi-ancestry GWAS further improved model performance, underscoring the need for ancestry-specific genetic studies -including the ongoing Egyptian PD GWAS- to refine risk prediction and clinical association analyses in underrepresented populations. Second, to investigate the genetic contributors to vascular parkinsonism (VaP), an understudied and clinically debated parkinsonian syndrome that often overlaps with other neurological and vascular diagnoses, we performed whole-exome sequencing on five clinically diagnosed cases. Several predicted deleterious variants were identified in prioritized genes implicated in parkinsonism or cerebrovascular disease. Notably, seven of these genes (LRRK2, PLA2G6, TGM6, BSN, UBR4, CD36, and NOTCH3) harbored deleterious variants in more than one patient. We observed same variants previously reported in relevant diseases with overlapping clinical features including PD, spinocerebellar ataxia, cerebral small-vessel disease, essential tremor and migraine with aura, alongside additional rare candidate variants in prioritized genes supported by low population frequencies, in-silico pathogenicity predictions, and literature evidence. Furthermore, we detected an enrichment of highly deleterious variants in genes involved in extracellular matrix (ECM) organization -including collagen genes- which is essential for the integrity of blood vessel walls and associated with cerebrovascular disease. Together, these findings may suggest a polygenic interplay involving parkinsonism-associated variants, vascular risk alleles, and ECM-related genes in shaping the genetic susceptibility to VaP. Both projects highlight the polygenic contributions to parkinsonism in Egyptians, with the first iv project characterizing the collective impact of known common polygenic variants, identified from European PD GWAS studies to be PD risk variants and the second uncovering rare deleterious variants potentially contributing to VaP. These findings emphasize the importance of population-specific genomic research for improving disease risk prediction and stratification, enhancing differentiation among overlapping parkinsonian phenotypes through a deeper understanding of their genetic contributors and ultimately supporting more equitable precision-medicine approaches for diverse populations.